Simulation and validation of thermography inspection for components produced by additive manufacturing. (August 2019) - Carvalho, Marta S.; Martins, Ana P.; Santos, Telmo G.
Abstract: This work presents the validation of the numerical simulations performed to support the development of Non-Destructive Testing for parts produced by Additive Manufacturing. The most common defects of these components are the voids and delamination, for which the Active Transient Thermography is one of the most reliable Non-Destructive Testing methods. However, a systematic and scientific insight on the thermal phenomena involved on Active Transient Thermography is needed to optimize the Non-Destructive Testing inspection parameters. Several representative case studies were experimentally tested and numerically simulated. For the case studies, samples of the polymeric material Nylon PA-12 were produced by Fused Deposition Modelling. The commercial code ANSYS is used for the calculation with the Finite Element Method of the thermal transient problem, using a numerical model which includes the three primary modes of heat transfer: conduction, convection, and radiation. Numerical simulation allowed a deeper insight of the thermal phenomena involved in the Non-Destructive Testing inspection, and it proves to be a useful tool for the selection of Non-Destructive Testing parameters.